Kajian konsentrasi kefir grain dan lama simpan dalam refrigerator terhadap kualitas kimiawi kefir rendah lemak - Manik Eirry Sawitri (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
Abstract :  1), 2percent (G2)dan 3 percent (G3)of milk volume and the second factor was storage time in refrigerator which were 0day(L0),7days(L7),14days(L14), 21 days(L21) and 28 days(L28 Keywords: kefir grains, storage time, refrigerator, low fat kefir). The variables measured were fat, protein, and alcohol content of kefir. Data were analyzed by analysis of variance and continued with Duncan.  The results of research showed that concentration of kefir grains and storage time in refrigerator had highly significant effect (P<0,01) on protein and alcohol content of kefir. Both treatment did not have significantly effect (P>0,05) on fat content of kefir. Interaction between both treatments had highly significant effect (P<0,01) on alcohol content of kefir.The conclusion of this research was apply 1 percent of kefir grains and maximum storage time in refrigerator for 21 days to produce kefir which appropriate with standard of fermentation milk.The objective of this research was to find out the influence of low fat milk in kefir processing with examined concentration on kefir grains and storage time in refrigerator to the fat, protein and alcohol content. This research was also to determined the concentration of kefir grains which appropriate to the standard of fermentation milk and as an information for practician and industry related to the research product. The materials used kefir that made from low fat milk (1% fat content), the research method was using Factorial Randomized Block Design (3X5). The first factor was concentration of kefir grains which were 1 percent(G